Implementation of Student Centered Learning Model in Improving Students’ Democratic Attitudes - Sartika, Meiliza (International Journal of Students Education, 2025)
This study aims to determine how to improve students’ democratic attitudes by using a student-centered learning model. The application of a democratic system in the classroom not only functions to create a more inclusive atmosphere, but also to build students’ social and leadership skills. A democratic attitude in the classroom is a behavior possessed by students and teachers where they have freedom of opinion, respect each other, and are not selfish with each other. In the context of higher education, the requirements for active learning are: students are responsible for their learning activities, students are cooperative, collaborative, and supportive, students are accountable for their learning outcomes, and the class has a student-centered atmosphere. This is applied in the higher education curriculum, namely the KKNI curriculum which requires the implementation of learning. This study uses the Literature Review method by searching for several research results from journals that are relevant or in accordance with the problems studied from several indexers such as Google Scholar, Basicedu, Sinta, and so on. The results of this study indicate that a student-centered learning model is very much needed in the learning process in order to improve students’ democratic feelings or attitudes and increase students’ learning motivation.